(untitled) (Світ фінансів, 2017)
Мрочковська Б. Використання коштів бюджетів місцевого самоврядування Польщі : сутнісно-теоретичні та класифікаційні аспекти. Розглянуто видатки бюджетів місцевого самоврядування Польщі з позиції їх сутнісних та класифікаційних ознак. Відзначено основні підходи до визначення складу видатків з позиції розмежування владних повноважень і завдань органів державної влади й місцевого самоврядування. Окреслено основні невирішені питання у цій сфері. Mrochkovska B. Use of facilities of budgets of local self-government of Poland : essence-theoretical and classifications aspects. The charges of budgets of local self-government of Poland are considered from position of their signs of essences and classifications. Basic approaches are marked to determination of composition of charges from position of differentiating of imperious plenary powers and tasks of public and local self-government authorities. Outlined basic open questions in this sphere.